The application of CEDAW Convention in Muslim countries: issues and challenges - Hamid, Abdul Ghafur@Khin Maung Sein (2013)
Most of the Muslim countries are parties to CEDAW and as parties they are bound by the convention and they have to make their laws to be in accord with it. Nevertheless, laws, in particular, family laws in Muslim countries are founded on Islamic law. This paper finds that Muslim countries are in a very difficult situation due to the incompatibility between CEDAW and Islamic law in a few hard core areas. The present paper does a thorough research on the reservations made by Muslim countries to get out of this dilemma. The paper also touches on the application of CEDAW in selected Muslim countries, in particular, Malaysia. The paper concludes that it is an extremely difficult and sensitive issue and the solution will largely depend on to what extent the CEDAW Committee can liberally interpret CEDAW’s principles of equality and non-discrimination in order that Muslim countries are able to comply with the most fundamental precepts of Islamic law and how much Muslim countries are prepared to accept the liberal interpretation of the Islamic law without compromising the most fundamental precepts.